Maine's Defense Dependency and its Effect on Economic Vitality - Lachance, Laurie (Maine Policy Review, 1994)
With the continuing shift to a non-Cold War defense posture, Maine is experiencing its share of economic hardship from the reduction in federal defense spending. In the following article, Maine State Economist Laurie Lachance describes the depth and breadth of Maine's defense dependency and outlines what that portends for the future of Maine's economy.
Keywords: Maine economy; defense conversion